UMAYYAD POTTERY IN (KHIRBET EDH-DHARIH) SOUTHERN OF JORDAN - Alhaija, Suhair Salah Abu; Sanajlih, Owis Mahmood (European Scientific Journal, ESJ, 2013)
ï»¿ï»¿The study aimed to explore the most pottery characteristics in Umayyad Period. The study depended on discovered pottery materials in the excavations in the site (Khirbet edh-Dharih) which was cited in the east side of Wadi Allo’oban on the way of the Temple which connected AlTafelah Governorate and AlKerak Governorate. The study focused on the discovered sample of the study in (Khirbet edh-Dharih) to identify them, classify them and extracted the pottery sample which resembled this study, which referred to Umayyad Period beside site historical importance during the Nepatiene, Byzantine and Islamic Periods. The researcher researched in Islamic Pottery in Umayyad Period in (Khirbet edh-Dharih) through the studying the history of the ancient research in the site and discussed the previous literature which were completed by roving as the surveys completed in the site, so excavations ancient constructions found in it: the Temple where found on it the Umayyad pieces of potteries. Palace, Napatiene house and the Cemetery. The Umayyad Pottery in the site were studied in the same site with the ways used in constructing Umayyad Pottery, the shape of the Potteries and the illustration of their artistic characteristics of them. The researcher classified the discovered potteries in reading the pottery pieces, the subject of the study, then classified each group according to its functions and the purpose of them. Potteries were drawn in measurement 1:1 in careful way, the researcher described the piece, identify its argil granules, Garnet, Quartz beside organic materials which they had been added to the Pottery, as identifying the color of the argil in using minis oil and identify how they were burned in the oven. The shape was described and surface manipulated added beside what they carry inside them or ornaments which performed on the outer surfaces of the potteries. Every pottery group were studied in mentioned the same examples to them and history by returning to the books published, essays which shed light on the historical side for the potteries, the subject of the study.